The Association of Nurses Caring Behavior with the Level of Patient Satisfaction, Harari Region, Eastern Ethiopia - Kibret H; Tadesse B; Debella A; Degefa M; Regassa LD (Nursing: Research and Reviews, 2022)
Haregeweyn Kibret,1 Barkot Tadesse,2 Adera Debella,2 Meron Degefa,2 Lemma Demissie Regassa3 1School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2Department of Maternity and Neonatal Nursing, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3Department of Epidemiology and Biostatistics, School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Haregeweyn KibretDepartment of Nursing, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, P.O. Box, 235, Harar, Ethiopia, Email haregeweynkibret@gmail.comPurpose: The extent to which nurses tailor their care to the patient’s specific needs has a direct impact on patient health outcomes. Satisfied people will have good communication with the health professional, which results in good care and health outcome, so this study aimed to assess the association of caring behavior of nurses with the level of patient satisfaction, in public hospitals of the Harari region, Eastern Ethiopia, from March 10 to April 10, 2021.Methods: A cross-sectional study was conducted among 300 nurses providing inpatient services and 345 randomly selected admitted patients in two public hospitals of Harari region, Eastern Ethiopia. Clinical nurse–patient interaction scale was used to assess the level of caring behavior. The level of patient satisfaction was measured using the patient satisfaction scale tool. We used structural equation modeling to determine the relationship of nurses caring behaviour and the level of patient satisfaction. The association was reported using coefficient (β) along with a 95% confidence interval. The statistical significance of the association was declared at P < 0.05.Results: According to this study, only 51.67% of the nurses had good caring behavior and 62.90% of the patients were satisfied with the nursing care they received. The nurses’ caring behavior score was increased by 41% (β=0.41; 95% CI: 0.20, 0.63) and (β=0.65; 95% CI: 0.48, 0.81) as nurses’ job satisfaction and work environment scores increased by one scale, respectively. Similarly, the score of patient satisfaction was increased by 2% (β=0.02; 95% CI: 0.01, 0.12) as the score of nurse caring behaviour was increased by one scale.Conclusion: Patient satisfaction increased as the nurses care behavior score increased, so nurses must continue to identify ways to evaluate and increase patient happiness, as well as illustrate the impact nurses have on patient satisfaction with hospital experience as a result of their treatment.Keywords: caring, nursing, caring behavior, patient satisfaction